INDIA-PAKISTAN-AFGHANISTAN ECONOMIC COOPERATION: A THEORETICAL APPROACH O REGIONAL INTEGRATION - MEHBOOB, Ahmed (CENTRAL ASIA AND THE CAUCASUS, 2017)
The paper posits that the persistent enmity among India, Pakistan, and Afghanistan, driven by jingoistic nationalism, has led to a situation where these countries prioritize security concerns over national development. This antagonism has reached such a critical point that it seems nearly irreparable. The paper suggests that this predicament could be mitigated by fostering globalization optimism, which entails promoting interstate cooperation, soft borders, and people-to-people contacts. Achieving these goals would require regional and economic integration—a concept that has been successfully implemented in Europe and has been widely discussed by scholars across various fields.The paper draws upon theoretical and historical studies, as well as practical insights gathered from organizations and stakeholders during a recent field trip to Pakistan. It highlights the failure of the New International Economic Order (NIEO) to implement its "program of action," which emphasized the importance of regional and interregional cooperation among developing countries. The NIEO aimed to create a unified community for economic development, but the concept of Collective Self-Reliance emerged as a significant alternative.The idea of Collective Self-Reliance, discussed extensively since the Non-Aligned Movement's Lusaka summit, focuses on enhancing technical and economic cooperation among developing countries. It is not intended to replace the existing economic order but to provide a practical means for these countries to address their worsening global economic conditions. Collective Self-Reliance promotes national self-sufficiency while facilitating cooperation among underdeveloped nations. However, it remains an auxiliary approach rather than a comprehensive solution. As the number of cooperating countries grows, collaboration tends to become more selective, making regional cooperation crucial.In summary, the concept of Collective Self-Reliance plays a crucial role in fostering regional cooperation among developing countries by encouraging both national self-reliance and collaborative efforts, particularly in the context of challenging global economic conditions.